Variability of signature whistle emission in a bottlenose dolphin unit off the eastern Ligurian coast (Italy) - Bonelli, Bianca; Bellingeri, Michela; Zanoli, Anna; Roella, Miryam; Favaro, Livio; Gnone, Guido (Biologia Marina Mediterranea, 2025)
Tursiops truncatus (Montagu, 1821) is a regularly present species in the Mediterranean Sea. This study aims to investigate the acoustic behaviour of this species in different contexts and group compositions. We carried out an identification of signature and non-signature whistles using the SIGID (SIGnature IDentification) method, and we compared whistles identified as primary signature whistles (necessary for the initial categorisation of signature whistles) with the secondary signature whistles (whistles with a known frequency modulation compared to previous categorisation). We used Pamguard to extract the whistle contours and the SIGID criterion to identify the signature whistles. We classified 1146 non-signature whistles and 234 signature whistles. Of these, 79 were the primary signature whistles, and 155 were the secondary signature whistles. Our results suggest a more extensive use of signature whistles in our study population than that the SIGID criterion can identify.